Assessing AI Integration in Islamic Higher Education: A Mixed-Methods Fishbone Diagram Analysis - Aan Ansori; Fitri Damyati; Syifa Amara Dhestyani (IJID (International Journal on Informatics for Development), 2024)
The integration of Artificial Intelligence (AI) in higher education has shown significant potential to improve the efficiency and effectiveness of learning. The strategic implementation of AI in State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri/ PTKIN) fosters innovative pedagogy and improved academic performance. This study employs the Fishbone Diagram approach to systematically analyze AI's impact on PTKIN’s education, identifying key factors influencing implementation. The method employs a reverse-cause analysis, mapping factors contributing to a primary issue, and identifying underlying causes and sub-factors. Findings highlight the crucial roles of technological infrastructure, human resource readiness, supportive policies, adaptive curriculum design, and organizational culture. This study underscores the necessity of integrated AI adoption frameworks in Indonesian Islamic higher education, harmonizing technological advancement with Islamic pedagogical principles. This study offers a foundational framework guiding PTKIN in developing sustainable and ethical AI policies. Comprehensive AI policies and strategies are essential for PTKIN to harmonize innovation with Islamic principles.